Landscape Functionality Analysis of Soil Surface Conditions in an Arid Zone: A Case Study of Lajaneh Piosphere, Iran - Shahriary, Eahsan; S, Shubhasmita; Langford, P (Annals of Arid Zone, 2019)
Livestock grazing changes landscape functionality, nutrient availability andsoil structure and surface conditions in dryland rangelands. A piosphere is a zone ofinteraction among vegetation, watering point and livestock. This study uses landscapeand soil indicators to evaluate the condition of the soil surface in Lajaneh piosphere,Shahrood, Iran. Lajaneh is in an arid region, with predominant land cover of Zygophyllumeurypterum, and grazed by camels, goats and sheep. We used landscape function analysis(LFA) and trigger-transfer-reserve-pulse (TTRP) to derive eleven soil surface indicatorswhich were measured and combined to calculate the three indices of infiltration, stabilityand nutrient cycling. One-way ANOVA and Tukeyâ€™s post hoc tests were used to findthe differences in infiltration, stability and nutrient cycling indicators among threedistances 10, 100 and 1000 m. Significant differences were found in infiltration, stabilityand nutrient cycling among at 10 m, 100 m and 1000 m from watering point. The threeindices of nutrient cycling, infiltration and stability increased with increasing distancefrom watering point. Our study showed the importance of vegetation patches andrunoff/runon processes in soil surface condition, and showed the results of grazingpressure on soil health centered on the â€œsacrifice zoneâ€ closest to the watering pointand decreasing with distance. We show that the LFA method is an effective measurefor monitoring soil surface health around watering points and piosphere, balancing thefeedbacks and offtakes based on the condition of soil surface indices.Key words: LFA, piosphere, arid zone, overgrazing, offtakes, feedbacks